Processing Pangek Lapuak Using Balango And Pariuak Stale - Zumairo, Siti; Elida, Elida; Fridayanti, Lucy; Gusnita, Wiwik (Universitas Negeri Padang, 2024)
Pangek lapuak is a typical food from Nagari Barulak which is made from goldfish and asam kosambi leaves as a natural ingredient to soften the bones. There are two types of processing equipment used in the processing process, namely balango and pariauk basi. Using different processing equipment will produce different qualities of pangek lapuak. This research aims to analyze the effect of the tools used on the quality of color, aroma, aroma texture and taste of pangek lapuak. This type of research is pure experiment (true experimental) using the Independent Sample T-test method. The data used is primary data obtained directly from 3 expert panelists by filling in the organoleptic test format for pangek lapuak using balango and pariauk basi. The data obtained was then tabulated in table form and a level test was carried out on each variable X1 and X2 to find out whether there was a mean comparison for these variables using the Independent Sample T-test. The results of the research show that there is an influence of the use of different processing equipment on the quality of the aroma and savory taste of fish with the highest result being the quality of the fragrant fish aroma of 3.89 (fragrant fish), for the fragrant aroma of the sauce with a value of 3.89 (the fragrant aroma of the sauce). while for the savory taste of fish it has a value of 3.67 (savory fish). The best quality test results for pangek lapuak were found in the use of balango.